Phenotyping the migraine patient - Cowan, Robert P. (Henry Stewart Talks, 2023)
Episodic migraine, Chronic migraine, Chronification of migraines, Risk factors of migraines, Allodynia, Sensitization, Hyperexcitability, Dysmodulation, Potential biomarkers, Functional MRI, Managing chronification